Innovative solutions in fluid-particle systems and renewable energy management - Tannous, Katia, 1962- (Engineering Science Reference, 2015)
"This book presents phenomenological, experimental, and theoretical research, as well as market criteria and business models concerning the development of small- and large-scale chemical and energy plants"--Provided by publisher.